Modern models of monopsony in labor markets: A brief survey - Orley C. Ashenfelter; Henry S. Farber; Michael R. Ransom (Institute for the Study of Labor (IZA), 2010)
This brief survey contains a review of several new empirical papers that attempt to measure the extent of monopsony in labor markets. As noted originally by Joan Robinson, monopsonistic exploitation represents the gap between the value of a worker's marginal product and the worker's wage, and it represents both a distortion in the allocation of resources and an income transfer away from workers. The evidence surveyed from a fairly broad range of labor markets suggests that monopsony may be far more pervasive than is sometimes suggested.
Keywords: J31; 330; Monopsony; imperfect labor markets; Arbeitsmarkt; Arbeitsnachfrage; Monopson; Unvollkommener Markt; Welt